2012
DOI: 10.1155/2012/637839
|View full text |Cite
|
Sign up to set email alerts
|

Acid Treatment of Titania Pastes to Create Scattering Layers in Dye-Sensitized Solar Cells

Abstract: In dye-sensitized solar cells (DSC) scattering layers are used to increase the path length of light incident on the TiO2film. This is typically achieved by the deposition of an additional TiO2layer on top of an existing transparent film and designed to trap light. In this work we show that a simple acid pretreatment can lead to the formation of a scattering “skin” on the surface of a single TiO2film performing a similar function to a scattering layer without any additional depositions. This is important in inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…This is in contrast to the result reported by Watson et al, in which the nitric acid treatment led to significant changes in the microstructures of the top surface of the electrode and alternation in the pore size of the TiO 2 . 27 These different results may be due to the different concentrations of nitric acid solutions used: we carried out with a 0.1 M (pH 1) nitric acid solution, whereas Watson et al performed with that of 2 M, which is 20 times more concentrated than ours.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…This is in contrast to the result reported by Watson et al, in which the nitric acid treatment led to significant changes in the microstructures of the top surface of the electrode and alternation in the pore size of the TiO 2 . 27 These different results may be due to the different concentrations of nitric acid solutions used: we carried out with a 0.1 M (pH 1) nitric acid solution, whereas Watson et al performed with that of 2 M, which is 20 times more concentrated than ours.…”
Section: ■ Results and Discussionmentioning
confidence: 62%
“…The recorded increase in reflectance is proportional to the wavelength (Figure 1b, Figure 2a), and higher for longer exposure to nitric acid ( Figure S2a, Supporting Information). Surface modifications of titania pastes upon treatment with nitric acid have been previously shown to increase the absorbance in the 400-800 nm wavelength range, enhancing the light-harvesting effectiveness of DSSCs, and the incident photon-to-current conversion efficiency because of increased forward scattering [41]. It was also found that the NO3 -ions produced after immersion in HNO3 may coat the TiO2 and block the path of backward electron transfer [42].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this current study is to develop techniques which could allow in situ measurement of the corrosion rates of metals in sealed cells, without the need for ex situ sampling of the DSC electrolyte. We have adapted two techniques used in other areas of DSC study, such as dye uptake kinetics, namely, diffuse reflectance UV-visible spectrophotometry (DR-UV/Vis) and time-lapse digital photography [15][16][17][18]. As both techniques employ thin electrolyte layers in contact with metal surfaces, any interaction of the coloured triiodide species with the metal can be rapidly quantified.…”
Section: Introductionmentioning
confidence: 99%